2011
DOI: 10.1590/s0037-86822011005000004
|View full text |Cite
|
Sign up to set email alerts
|

Monitoramento da suscetibilidade de populações de Triatoma sordida Stål, 1859 (Hemiptera: Reduviidae) ao inseticida deltametrina, na região Centro-Oeste do Brasil

Abstract: INTRODUÇÃO: Populações de Triatoma sordida Stål, 1859 foram investigadas quanto à suscetibilidade à deltametrina. MÉTODOS: Análise por meio de bioensaios por aplicação tópica em 11 populações de T. sordida procedentes dos Estados de Goiás, Mato Grosso e Mato Grosso do Sul. RESULTADOS: As estimativas de DL50 e RR50 demonstraram elevados níveis de suscetibilidade (DL50 < 1 e RR50 < 2). Entretanto, as análises do coeficiente angular da curva dose resposta revelaram que as populações de triatomíneos dos muni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
(8 reference statements)
1
12
0
Order By: Relevance
“…The susceptibility profi le of T. sordida in our study is similar to that by Obara et al (15) but unlike that by Pessoa et al (13) . However, the different toxicological profi les of deltamethrin in T. sordida populations from distinct locations in the same municipality (e.g., Frutal/Guilherme F. Correa and Frutal/ Aureliano N. Cruz), showed the complexity of the resistance phenotype, at both macro-and microgeographical levels, as observed by Pessoa et al (16) in their studies of Brazilian T. infestans populations from Rio Grande do Sul.…”
Section: Ethical Considerationssupporting
confidence: 87%
See 2 more Smart Citations
“…The susceptibility profi le of T. sordida in our study is similar to that by Obara et al (15) but unlike that by Pessoa et al (13) . However, the different toxicological profi les of deltamethrin in T. sordida populations from distinct locations in the same municipality (e.g., Frutal/Guilherme F. Correa and Frutal/ Aureliano N. Cruz), showed the complexity of the resistance phenotype, at both macro-and microgeographical levels, as observed by Pessoa et al (16) in their studies of Brazilian T. infestans populations from Rio Grande do Sul.…”
Section: Ethical Considerationssupporting
confidence: 87%
“…Despite reports of persistent T. sordida infestation, only two studies have determined the susceptibility of Brazilian populations of this triatomine to insecticides (13) (15) . Pessoa (13) showed the deltamethrin toxicological profile in eleven peridomestic T. sordida populations collected from areas with reports of persistent infestation, in the North of Minas Gerais.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Obara et al 12 , there are no records of Brazilian T. sordida populations resistant to deltamethrin. A susceptibility study of 11 populations from the center-west region of Brazil revealed RR 50 values ranging from 1.05 to 1.48.…”
Section: Discussionmentioning
confidence: 99%
“…The RR is calculated from SRL lethal doses; thus, the resistance level obtained may consequently interfere, in the future developments to be adopted by the managers involved with Triatominae control in the fi eld. As an example, the RR 50 observed by Obara et al (51) for T. sordida populations treated with deltamethrin allowed the study population to be classifi ed as susceptible to the tested insecticide, leading to the recommendation of time line monitoring. However, if the authors had used the SRL adopted by Pessoa (31) , the RR 50 would have increased nine fold.…”
Section: Methodological Difficultiesmentioning
confidence: 99%